2023
DOI: 10.1039/d3lc00647f
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-accelerated high-throughput screening of antibiotic combinations on a microfluidic combinatorial droplet system

Abstract: The microfluidic platforms have been employed as an effective tool for drug screening, which exhibit the advantages of lower reagent consumption, higher throughput and higher degree of automation. Despite the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…167,168 However, by integrating microfluidic technology and AI, the screening process from drug design, synthesis to testing can be transformed, which is of significant importance in accelerating drug development. 168–171 For example, Grisoni et al pioneered the strategy of combining deep learning-based molecular design with microfluidic automated synthesis (Fig. 7A).…”
Section: How Can High-throughput Microfluidic Systems Benefit From Ai?mentioning
confidence: 99%
“…167,168 However, by integrating microfluidic technology and AI, the screening process from drug design, synthesis to testing can be transformed, which is of significant importance in accelerating drug development. 168–171 For example, Grisoni et al pioneered the strategy of combining deep learning-based molecular design with microfluidic automated synthesis (Fig. 7A).…”
Section: How Can High-throughput Microfluidic Systems Benefit From Ai?mentioning
confidence: 99%
“…Microfluidic technology has emerged as a response to multidisciplinary convergence. It utilizes chemistry, fluid physics, microelectronic materials, nanotechnology, and biotechnology [7]. By manipulating small amounts of fluids in channels at the micrometer or nanometer scale, it brings the screening process onto a chip, achieving automation and intelligence [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…35−38 For instance, Huang et al experimentally reported an artificial intelligence-accelerated high-throughput evaluation system for rapid and systematic screening of drug combinations and solved the problem in which conventional manual or semiautomatic data analysis was unable to analyze large numbers of data sets generated during the screening process. 39 Pathak et al proposed a method for developing an artificially intelligent nanopore by integrating supervised machine learning and transverse quantum transport technology with a graphene nanopore. The model could predict the transmission function of all other nucleotides after training with data sets generated from all the orientations of any nucleotide inside the nanopore.…”
mentioning
confidence: 99%
“…In the process of multiparameter size discrimination, the accurate processing and analysis of multidimensional data are critical and important. Artificial intelligence (AI) is a powerful and evolving technology in providing predictions and processing multidimensional data with minimal human intervention due to its time-saving, labor-saving, and deep learning advantages. AI has not only been the theoretical research of computer science but also turns to applications across many fields of science and medicine, such as drug design, medical imaging, and so on. For instance, Huang et al experimentally reported an artificial intelligence-accelerated high-throughput evaluation system for rapid and systematic screening of drug combinations and solved the problem in which conventional manual or semiautomatic data analysis was unable to analyze large numbers of data sets generated during the screening process . Pathak et al proposed a method for developing an artificially intelligent nanopore by integrating supervised machine learning and transverse quantum transport technology with a graphene nanopore.…”
mentioning
confidence: 99%